A Bibliometric Analysis Ethical Perspectives on SDGs Based Education Goals Using VOSViewer - Sumadisastro, Witzir; Robandi, Babang; Fahrizal, Diki (Universitas Pendidikan Indonesia, 2024)
This study investigates the integration of ethical perspectives into the frameworks of Education for Sustainable Development (ESD) and Society 5.0, with a focus on their alignment with the Sustainable Development Goals (SDGs). Utilizing a bibliometric analysis, the research examines academic and professional literature published between 2010 and 2024. Data was collected from Google Scholar using keywords such as